2022
DOI: 10.1111/jgh.15813
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal interleukin‐8 expression as a predictor of subsequent relapse in ulcerative colitis patients with Mayo endoscopic subscore 0

Abstract: This study was partly supported by these funds. Y. N. is an associate editor of "Digestion." Neither the funding agency nor any outside organization participated in the study design or had any competing interests. These companies approved the final version of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Studies have shown that IL-4 in UC could induce monocytes and eosinophils to participate in inflammatory response and stimulate mast cell proliferation, thus promoting inflammatory response and aggravating the degree of UC. 78 , 79 The level of peripheral 5-HT, a pro-inflammatory factor, which could regulate cellular immune function, promote emission of IFN-γ and other inflammatory factors, 80 and also aggravate inflammatory response of UC, was positively correlated with the severity of UC, 80 , 81 Taken together, DSS could increase the abundance of Clostridium_sensu_stricto_1 relative pro-inflammatory factors, promotes the release of IL-4, 5-HT, TNF-α and IFN-γ, which could promote intestinal inflammation, leading to ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that IL-4 in UC could induce monocytes and eosinophils to participate in inflammatory response and stimulate mast cell proliferation, thus promoting inflammatory response and aggravating the degree of UC. 78 , 79 The level of peripheral 5-HT, a pro-inflammatory factor, which could regulate cellular immune function, promote emission of IFN-γ and other inflammatory factors, 80 and also aggravate inflammatory response of UC, was positively correlated with the severity of UC, 80 , 81 Taken together, DSS could increase the abundance of Clostridium_sensu_stricto_1 relative pro-inflammatory factors, promotes the release of IL-4, 5-HT, TNF-α and IFN-γ, which could promote intestinal inflammation, leading to ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of some pro-inflammatory cytokines and chemokines correlates to endoscopic disease activity. ( 28 , 29 ) We analyzed mRNA expression of cytokines and chemokines based on MES. We could not perform statistical analyses since three UC flare-up patients were judged as MES 2 ( n = 2) and MES 3 ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…( 33 , 34 ) UC relapse was defined as aggravation of UC-associated symptoms and UC aggravation based on endoscopic findings. ( 28 , 29 ) Endoscopic and histological disease activities were assessed by MES and Nancy histological index, respectively. The clinical characteristics of the patients with active UC not associated with COVID-19 vaccination are summarized in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ILs are important cytokines involved in a variety of inflammatory pathways, and there have been many studies on their roles in the development, pathogenesis, and treatment mechanism of IBD ( 9 ). For instance, a prospective observational study examined the expression of mucosal cytokines in 55 UC patients and detected the expression level of 10 types of ILs after their recurrence, and confirmed that IL-8 is the most potent predictor of UC recurrence ( 10 ). Meanwhile, clinical research evidence also supports the role of various chemokines in the pathogenesis of IBD.…”
Section: Introductionmentioning
confidence: 92%